THE IMPORTANCE OF SPORTS MEDICINE IN THE EDUCATIONAL PROCESS - Akbarova D. R. (Modern American Journals, 2025)
In the article, the pedagogical importance of Sports Medicine in the educational process and its approach to education, its importance in improving the physical condition and health of students, but also in ensuring their intellectual and emotional development. covered in detail.
Keywords: Physical education teacher, sports medicine, physical condition, intellectual, emotional, medical group, medical knowledge, motivation, strategy, choice, health.